Empowering the Indonesian Community in Penang through the Development of Plastic Waste Collection Businesses to Reduce Greenhouse Gas Emissions - Dianta Ginting; Kontan Tarigan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Penang’s mounting plastic pollution and limited landfill space coincide with precarious livelihoods for Indonesian migrant workers. This community-empowerment initiative trains migrants to convert plastic waste into income-generating micro-enterprises. Participants master the full chain—from organising door-to-door collection routes and safe household sorting to operating low-cost shredding units and baling plastics for bulk sales to recycling plants. Cooperative governance and basic cost tracking ensure transparent profit sharing and long-term viability. Early results show substantial diversion of recyclable plastics from landfills, measurable cuts in projected greenhouse-gas emissions, and higher monthly earnings for more than fifty migrant households. Shared ownership of collection and shredding operations also strengthens social cohesion and community resilience. The scalable model demonstrates how linking practical waste handling to locally rooted business activities can advance circular-economy goals, improve migrant livelihoods, and foster sustained environmental stewardship in Penang and comparable underserved settings.